The law relating to documentary credits from a South African perspective with special reference to the legal position of the issuing and confirming banks - Hugo, Charl Francois (Stellenbosch: University of Stellenbosch, 2010)
Thesis ((LLD (Law))--University of Stellenbosch, 1996.